Does the transition from face-to-face to face-to-screen improve oral health literacy? A non-inferiority randomized controlled trial - Negar Ebrahimi; Katayoun Sargeran; Reza Yazdani; Ahmad Reza Shamshiri (BMC Oral Health)
Abstract Background In recent years, more attention has been paid to virtual education methods in the field of oral health. Oral health literacy (OHL) plays a major role in reducing oral health inequalities. Individuals with inadequate health literacy are more susceptible to oral disorders. This study was a parallel randomized controlled trial with a non-inferiority design that aimed to compare a virtual educational intervention with traditional in-person education to improve OHL. Methods This study was conducted in adults visiting a university dental school, from February 2022 to May 2023. After the inclusion and exclusion criteria were checked and informed consent was obtained, the participants were randomly allocated into two groups by balanced block randomization. One group received in-person education in the waiting room, and the other received an educational video through an online messenger. The Oral Health Literacy Adult Questionnaire (OHL-AQ) assessed participants’ OHL levels before, immediately after, and three months after the intervention. The researchers who analysed the data were blinded. Generalized estimating equation (GEE) analysis was used to compare the groups (P < 0.05). The non-inferiority margin was determined using the fixed-margin method. Results In total, 149 individuals participated. Seventy-five patients were randomly allocated to the in-person group, and 74 were allocated to the virtual group; their data were analysed. GEE analysis revealed no significant difference in the change of OHL scores immediately after the intervention between the two groups (P = 0.07). However, at the three-month follow-up, the in-person group exhibited a significantly greater improvement in OHL scores compared to the virtual group (P = 0.03). After three months, virtual education was inferior to in-person education, unlike in the immediate post-test. Conclusion After three months, an online video sent in a messenger environment was less effective than traditional in-person education in improving OHL. Trial registration The trial protocol was registered in the Iranian Registry of Clinical Trials (IRCT) on 08–02-2022, (IRCT20220106053643N1|| http://www.irct.ir/ ).